The genetic diversity of Paeonia anomala (Paeoniaceae), as indicated by nuclear ITS and plastid ycf1 molecular markers - Degtjareva Galina (EDP Sciences, 2021)
Variability of nuclear ITS rDNA and plastid ycf1 gene was studied to elucidate genetic diversity of Paeonia anomala (Paeoniaceae), which possesses the most extensive range among all species of the genus. Sixteen populations were sampled across the entire distribution range of the species. The principal coordinate analysis suggested the existence of three ycf1 haplotype groups distributed in distinct geographical locations. For ITS region, no variability throughout the range was found; only samples of P. anomala from its north-western range margin (the Kola Peninsula) are characterized by unique nucleotide substitutions.